(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The new ethics of artificial intelligence proposed by M. Gabriel is critically evaluated. It is argued that, unlike human intelligence, artificial intelligence (AI) is devoid of normative dimension, or, equivalently, of sensitivity to context. Gabriels view conflicts with J. Benoists contextual realist approach to ethics and T. Williamsons moral realism, according to which it is not principles that are primary but moral perception in context, paradigmatic examples of moral knowledge. The approaches of Gabriel, D. Andler, L. Floridi, Russell to AI are considered and compared. It is proposed to adopt Andlers principle of moderation. It is argued that AI systems imitate intelligence, agency, autonomy, ethics. A realistic conception of AI is contrasted with its idealistic conception.